2005
DOI: 10.1111/j.1365-2036.2006.02739.x
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome proliferator‐activated receptor‐gamma Pro12Ala polymorphism, Helicobacter pylori infection and non‐cardia gastric carcinoma in Chinese

Abstract: SUMMARY BackgroundPeroxisome proliferator-activated receptor c inhibits the growth and induces apoptosis of gastric cancer cells. A common polymorphism at codon 12 of this gene (Pro12Ala) has been shown to confer protection against diabetes and colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 29 publications
3
23
0
Order By: Relevance
“…Indeed, GC risk was found to be increased in Ala12 allele carriers of PPARγ gene in the presence of H.pylori infection in previous studies (Liao et al, 2006;Prasad et al, 2008). Further analysis in GC patients with presence of H.pylori infection seems to be mandatory to clarify the association between H.pylori infection and PPARγ polymorphism in GC development.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Indeed, GC risk was found to be increased in Ala12 allele carriers of PPARγ gene in the presence of H.pylori infection in previous studies (Liao et al, 2006;Prasad et al, 2008). Further analysis in GC patients with presence of H.pylori infection seems to be mandatory to clarify the association between H.pylori infection and PPARγ polymorphism in GC development.…”
Section: Discussionmentioning
confidence: 90%
“…We found that the patients with Ala12 allele carriers had 1.57-fold (95%CI: 1.103-2.238) increased risk of progression to GC. Regarding the association between Ala 12 polymorphism of PPAR γ gene and GC risk, Liao et al (2006) reported 2.5-fold increased risk in Chinese, Prasad et al (2008) reported 2.14-fold increased risk in Indian, and Tahara et al (2008). reported 2.4-fold increased risk in Japanese population of progression to GC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two PPARÁ common polymorphisms, a C➝G transition in exon B resulting in a proline to alanine exchange at amino acid position 12 (P12A) (OMIM *0002; rs1801282) and a C➝T transition at position 161 in exon 6 (C161T) (OMIM *0009; rs3856806) have been identified and found to be associated with the risk of type 2 diabetes and cardiovascular events (4,5). In recent years evidence shows that both variations may also influence individual susceptibility to several types of cancer, such as those that occur in the central nervous system (6), lung (7,8), stomach (9)(10)(11)(12), biliary tract (13), colorectum (14)(15)(16)(17)(18)(19)(20)(21)(22), bladder (23), breast (24)(25)(26)(27), ovaries (28), endometrium (29), prostate (30)(31)(32), kidney (28) and skin (33). However, the observed results of these studies were inconsistent.…”
Section: Introductionmentioning
confidence: 99%